Biochemistry of opioid (morphine) receptors : binding, structure and molecular modelling - Benyhe, Sándor; Zádor, Ferenc; Ötvös, Ferenc (Acta Biologica Szegediensis, 2015)
Morphine is the most widely used compound among narcotic analgesics and remains the gold standard when the effects of other analgetic drugs are compared. The most characteristic effect of morphine is the modulation of pain perception resulting in an increase in the threshold of noxious stimuli. Antinociception induced by morphine is mediated via opioid receptors, namely the μ-type opioid receptor. Apart from the μ-opioid receptor, two other classical opioid receptors κ- and δ- and one non-classical opioid receptor, the nociceptin receptor was discovered and cloned so far. At the same time endogenous opioids were also discovered, such as enkephalins, endorphins, and dynorphins. The opioid receptors together with the endogenous opioids form the so called endogenous opioid system, which is highly distributed throughout the body and apart from analgesia it has several other important physiological functions. In this article we will review the historical milestones of opioid research − in detail with morphine. The review will also cover the upmost knowledge in the molecular structure and physiological effects of opioid receptors and endogenous opioids and we will discuss opioid receptor modelling − a rapidly evolving field in opioid receptor research.